Hello, there!
What's the answer to the equation 4(x + 7) = 9(x - 1) + 22
Answer: x = 3
------------------------------------------------------------------------------------------------------
Step-by-step explanation:
First, let's simplify this
4 * x = 4x
4 * 7 = 28
Now, we have 4x + 28 = 9(x - 1) + 22
Now, let's simplify the right side by using the distributive property as well.
9 * x = 9x
9 * -1 = -9
Now, we have 4x + 28 = 9x -9 + 22
Let's combine like terms on the right side
-9 + 22 = 13
Npw, we have 4x + 28 = 9x + 13
Let's isolate the x. To do this, we will first subtract 28 from each side.
4x + 28 = 9x + 13
-28 -28
4x = 9x - 15
Now, we will subtract 9x from each side.
4x = 9x - 15
-9x -9x
-5x = -15
Now, we will multiply each side by -1 to make x a positive number.
-5x = -15
*-1 *-1
5x = 15
Finally, we will simplify this completely. To do this, we will divide each side by 5.
5x = 15
--- ----
5 5
x = 3
Our final answer is x = 3
I hope I helped!
Let me know if you need anything else!
~ Zoe